2003
DOI: 10.1002/cncr.11688
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the expected positive correlation between breast tumor size and lymph node status in BRCA1‐related breast carcinoma

Abstract: BACKGROUNDA positive correlation between breast tumor size and the number of axillary lymph nodes containing tumor is well established. It has been reported that patients with BRCA1‐related breast carcinoma are more likely than patients with nonhereditary breast carcinoma to have negative lymph node status. Therefore, the authors questioned whether the known positive correlation between tumor size and lymph node status also was present in women with BRCA1‐related breast carcinomas.METHODSThe relation between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
48
0
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(67 citation statements)
references
References 33 publications
15
48
0
4
Order By: Relevance
“…Future studies should evaluate the usefulness of this marker for more accurately predicting the probability of carrying a BRCA1 mutation, as has been suggested for CK5/6. Interestingly, previous studies have shown a characteristic pattern of metastatic spread in familial BRCA1 tumors consisting of a low incidence of lymphatic spread to the axillary nodes, but a high incidence of hematogenous spread, mainly to the lung and brain (53,54). This pattern of spread is similar to that observed in the work of Minn et al (8) and in the present series, and suggests that it is related with a basal phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…Future studies should evaluate the usefulness of this marker for more accurately predicting the probability of carrying a BRCA1 mutation, as has been suggested for CK5/6. Interestingly, previous studies have shown a characteristic pattern of metastatic spread in familial BRCA1 tumors consisting of a low incidence of lymphatic spread to the axillary nodes, but a high incidence of hematogenous spread, mainly to the lung and brain (53,54). This pattern of spread is similar to that observed in the work of Minn et al (8) and in the present series, and suggests that it is related with a basal phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…2). This result confirms and extends our original observations discussed above (53,54), and given that basal breast cancers are associated with a worse prognosis than nonbasal breast cancers (8,9,55), suggests that the mechanism of metastatic spread may be different for this subtype of breast cancer. This view is supported by the multivariable proportional hazards model, including terms for interactions among P-cadherin, tumor size, and lymph node status ( Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…We previously showed that the expected relationship between increasing tumor size and increasing number of axillary nodes involved by metastatic tumor does not hold equally for BRCA1-related and other types of breast cancer (53). We later showed that this might be a general property of basal breast cancers (11), and this conjecture is supported by the data shown here.…”
Section: Discussionsupporting
confidence: 72%
“…It has been reported than more than 70% of BRCA1 tumors are grade 3, compared with 35% in sporadic cancer (Lakhani et al, 1997(Lakhani et al, , 2000Armes et al, 1998;Lynch et al, 1998;Quenneville et al, 2002;Goffin et al, 2003;Palacios et al, 2003;Eerola et al, 2005a). Other interesting aspects described in BRCA1 tumors are the scarce or absent ductal in situ component accompanying the invasive ductal component (Lakhani et al, 1997), and the disruption of the expected positive correlation between breast tumor size and lymph node status (Foulkes et al, 2003a). These two aspects of BRCA1 tumors have been associated with the fast growth of these tumors, often presented as interval cancers (Brekelmans et al, 2001).…”
Section: Morphology Of Brca1-and Brca2-associated Tumorsmentioning
confidence: 99%